When a Warning Sign is Not a Warning Sign: Chilaiditi’s Sign in a Patient with Heart Failure and Epigastric Hernia - Bhatta, Surendra Prasad; Timilsina, Saroj; Atreya, Alo (Birat Journal of Health Sciences, 2018)
Malposition of hepatic flexure of colon in sub diaphragmatic space, Chilaiditi syndrome, is usually an asymptomatic anatomical aberrancy of position. It is usually noted as a coincidental finding in chest X-ray. We present a case of 63 years old male who presented as an outpatient in the department of general medicine in rural hospital. The patient had features of heart failure and also had Chilaiditi syndrome as an incidental finding. This case is presented to remind ourselves of a harmless condition in the myriad of grave conditions that account for gas under the diaphragm in a chest X-ray. Birat Journal of Health Sciences Vol.2/No.3/Issue 4/Sep- Dec 2017, Page: 300-302